2022
DOI: 10.3390/s22041627
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive Techniques for the Condition and Structural Health Monitoring of Wind Turbines: A Literature Review of the Last 20 Years

Abstract: A complete surveillance strategy for wind turbines requires both the condition monitoring (CM) of their mechanical components and the structural health monitoring (SHM) of their load-bearing structural elements (foundations, tower, and blades). Therefore, it spans both the civil and mechanical engineering fields. Several traditional and advanced non-destructive techniques (NDTs) have been proposed for both areas of application throughout the last years. These include visual inspection (VI), acoustic emissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 266 publications
(223 reference statements)
0
29
0
Order By: Relevance
“…In‐plane shear strength of the CFRP specimens predicted for different testing temperatures using different prediction models [ 5,26,27 ] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In‐plane shear strength of the CFRP specimens predicted for different testing temperatures using different prediction models [ 5,26,27 ] …”
Section: Resultsmentioning
confidence: 99%
“…However, the experimental inplane shear strength fits well with the Hawileh model. It can be concluded that for the properties which relies mostly on the fiber orientation and fiber properties, F I G U R E 8 Tensile strength of the CFRP specimens predicted for different testing temperatures using different prediction models [5,26,27] F I G U R E 9 In-plane shear strength of the CFRP specimens predicted for different testing temperatures using different prediction models [5,26,27] modified Gibson and Nadjai model can be used. And Hawileh model can be used for predicting the properties that rely on the fiber-matrix interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide safety and efficiency, the technical operation of these structures is ensured through regular periodic inspections (surveys). To survey structures, non-destructive techniques (NDTs) are mainly used, like ultrasound, eddy current, X-ray and others [ 1 , 2 ]. To be applied on structures like wind turbines or aircrafts, these techniques require stop of operation.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several sensing technologies have been applied to the online monitoring of operating wind turbines [ 6 , 7 ]. Chen et al [ 8 ] collected monitoring signals of acoustic emission systems from commercial wind fields, which were used for health condition assessment of the wind turbine blade (WTB).…”
Section: Introductionmentioning
confidence: 99%